A pilot of Blood-First diagnostic cell free DNA (cfDNA) next generation sequencing (NGS) in patients with suspected advanced lung cancer. (March 2022) - Cui, Wanyuan; Milner-Watts, Charlotte; McVeigh, Terri P.; Minchom, Anna; Bholse, Jaishree; Davidson, Michael; Yousaf, Nadia; MacMahon, Suzanne; Mugalaasi, Hood; Gunapala, Ranga; Lee, Richard; George, Angela; et al.
Highlights: Blood-first NGS for suspected NSCLC led to timely treatment decisions during COVID19. 22% of patients commenced targeted therapy based on cfDNA NGS without tissue NGS results. cfDNA NGS detected 30 (61%) tier 1 variants: 20 additional to tissue testing alone. Time to results was shorter for cfDNA NGS compared to standard-of-care tissue tests. A blood-first approach can improve the speed and accuracy of therapeutic decisions. Abstract: Introduction: The diagnostic pathway for lung cancer can be long. Availability of front-line targeted therapies for NSCLC demands access to good quality tissue for genomic sequencing and rapid reporting of results. Diagnosis of lung cancer and availability of tissue was delayed during the COVID-19 pandemic. Methods: A pilot study assessing Guardant360™ cfDNA-NGS in patients with radiological-suspected advanced-stage lung cancer was performed at an academic cancer centre during COVID-19. Variants were tiered using AMP/ASCO/CAP guidelines and discussed at a tumour molecular board. The primary endpoint was the proportion of patients who commenced targeted treatment based on cfDNA-NGS results without tissue molecular results, predicted to be ≥ 10%. Results: Between April 2020-May 2021, 51 patients were enrolled; 49 were evaluable. The median age was 71 years, 43% were never-smokers, 86% had stage IV disease. 80% of evaluable cfDNA-NGS were informative (tumour-derived cfDNA detected). cfDNA-NGS detected 30 (61%) AMP/ASCO/CAP tier 1 variants, including 20 additional tier 1 variants compared to tissue testing. Three patients with non-informative cfDNA-NGS had tier 1 variants identified on tissue testing. Eleven (22%; 95%CI 12%-27%) patients commenced targeted therapy based on cfDNA-NGS results without tissue molecular results, meeting the primary endpoint. Median time to results was shorter for cfDNA-NGS compared to standard-of-care tissue tests (9 versus 25 days, P < 0.0001). Conclusion: Blood-first cfDNA-NGS in NSCLC patients increased the breadth and rapidity of detection of actionable variants with high tissue concordance and led to timely treatment decisions. A blood-first approach should be considered to improve the speed and accuracy of therapeutic decision-making.